Learning media projects with YouTube videos: a dynamic tool for improving mathematics achievement - Imam Kusmaryono; Mochamad Abdul Basir (Institute of Advanced Engineering and Science, 2024)
This research was designed with a descriptive research approach. The research objectives of the study were to: i) investigate the impact of the project task of learning video media on prospective teachers and students; ii) analyze the important role of instructional video media as a learning assistant for students; and iii) describe the function of instructional video media in increasing students’ interest and achievement in learning. This research involved 100 participants consisting of 10 students of a teacher education study program (prospective teachers), and 90 junior high school students. The researchers collected data through tests; questionnaires; and interviews. Researchers analyzed the data through descriptive statistical analysis. The results of the study indicated that the project assignment of making videos for learning (on a YouTube channel) provided a positive impact on learning experiences for teachers (prospective teachers) and students. Mathematics learning video media has a role as a digital native that may help overcome the limitations of students’ knowledge and understanding. Mathematics learning videos on the YouTube channel can be a dynamic tool to increase students’ interest (as an attention, and affective function) and to improve students’ mathematics learning achievement (as a cognitive function).